Possible genetic determinants of gentamicin resistance in listeria monocytogenes - Ng, Jamie May Ling (2023)
Listeria monocytogenes is a Gram-positive foodborne pathogen capable of causing a foodborne infection known as listeriosis. There are two main types of listeriosis: non-invasive and invasive form which is often associated with a high mortality and hospitalisation rate among susceptible individuals. Gentamicin, used as an adjunct therapy with ampicillin, remains the treatment of choice for the life-threatening and invasive listeriosis. Nevertheless, there is little data on gentamicin resistance determinants in L. monocytogenes. The main objective of the study was to identify possible genetic determinants of gentamicin resistance in L. monocytogenes. In this study, a gentamicin-resistant mutant, B2b, was derived from L. monocytogenes ATCC 19115 by using the Luria-Delbrück experiment to determine the target of resistance in L. monocytogenes. Wholegenome sequencing was carried out to identify the mutation site of resistance. The mutant was also characterised using antimicrobial susceptibility testing and PCR. The gentamicin resistance in B2b was caused by a 10-bp deletion in atpG2 which encodes a gamma subunit of the ATP synthase in L. monocytogenes. For biological validation by using reverse genetics, complementation and allelic exchange mutagenesis were carried out. Complementation of B2b with the wildtype atpG2 reverted the resistant phenotype back to its sensitive state. When the same mutation was introduced into the wild-type ATCC 19115 via allelic exchange, the development of gentamicin resistance was observed. The ATP level of B2b was significantly lower than the wild-type ATCC 19115, suggesting that the ATP production in B2b was potentially hampered by the atpG2 mutation. Using atpG2 PCR, various other mutations were identified in most of the gentamicin resistant mutants derived from ATCC 19115, indicating that atpG2 mutations could be a major driving force of gentamicin resistance in L. monocytogenes. In addition, the mutation from B2b, when introduced into L. ivanovii, also caused gentamicin resistance in this Listeria species. In conclusion, atpG2 mutations appear to be important determinants of gentamicin resistance not only in L. monocytogenes but possibly also in other Listeria species. These mutations could be a cause of treatment failure in Listeria infections treated with gentamicin. A better understanding of resistance mechanisms in L. monocytogenes is essential for the clinical management of potentially lifethreatening foodborne infections caused by this organism. By adding new gene targets to routine molecular drug susceptibility tests, it will be possible to quickly identify strains that are resistant to gentamicin and choose the best course of treatment. Through the development of new drugs or drug combinations based on resistance mechanisms, it also can help to curb the global spread of gentamicin resistance.